American government 2e - Krutz, Glen S.; OpenStax College (OpenStax, Rice University, 2019)
American Government 2e is designed to meet the scope and sequence requirements of the single-semester American Government course. This title includes innovative features designed to enhance student learning, including Insider Perspective features and a Get Connected module that shows students how they can get engaged in the political process. The book provides an important opportunity for students to learn the core concepts of American Government and understand how those concepts apply to their lives and the world around them.
Students and the System -- Individual Agency and Action -- Toward Collective Action: Mediating Institutions -- Delivering Collective Action: Formal Institutions -- The Outputs of Government.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references (pages 699-757) and index.
PDF, AG2-2019-000(02/19)-RS (viewed 11 March 2019).
Keywords: United States -- Politics and government -- Textbooks; Political science -- United States -- Textbooks; Electronic books